Identifying HER2 from serum‐derived exosomes in advanced gastric cancer as a promising biomarker for assessing tissue HER2 status and predicting the efficacy of trastuzumab‐based therapy. (8th October 2022) - Li, Qian; Lv, Minzhi; Lv, Lihua; Cao, Nida; Zhao, Aiguang; Chen, Jiayan; Tang, Xi; Luo, Rongkui; Yu, Shan; Zhou, Yan; Cui, Yuehong; Guo, Wei; et al.
Abstract: Purpose: This study aimed to evaluate the clinical relevance of exosomal HER2 (Exo HER2) level in assessing the tissue HER2 status and predicting the efficacy of trastuzumab treatment. Methods: In this prospective study, patients with advanced gastric cancer (AGC) from three hospitals between August 2016 to November 2020 were enrolled. The Exo HER2 level was detected by enzyme‐linked immunosorbent assay. Receiver operating characteristic curve (ROC) was drawn referring to the HER2 tissue status to assess the diagnostic value of Exo HER2. Cox proportional hazards regression and logistic regression were used to evaluate the association between Exo HER2 and progression‐free survival (PFS), overall survival (OS), and objective response rate (ORR) in patients who received trastuzumab‐based first‐line therapy. Results: In this study, 242 patients with advanced or metastatic gastric adenocarcinoma were registered. Of these, 238 AGC patients were eligible for evaluating serum‐derived exosome HER2 diagnostic value, including 114 HER2‐positive. Finally, 64 were eligible for efficacy analysis. The area under the ROC curve was 0.746. The optimal cutoff value for diagnosing tissue HER2‐positive status was 729.95 ng/ml, with a sensitivity of 66.7% and a specificity of 74.2%. In 64 patients treated with trastuzumab, higher baseline Exo HER2 level indicated better prognosis. 844 ng/ml and 723 ng/ml were the right cutoffs for distinguishing the population with superior PFS (hazard ratio [HR] = 0.41, P = 0.017) and OS (HR = 0.30, P < 0.001), respectively. Conclusion: Serum exosomal HER2 level might serve as an effective biomarker for assessing tissue HER2 status in AGC and screening the potential patients who might benefit from anti‐HER2 therapy. Abstract : In this prospective multi‐centers study, HER2 in serum‐derived exosome (Exo HER2) from patients with advanced or metastatic gastric adenocarcinoma (AGC) were analyzed for its diagnostic value and predictive value for trastuzumab therapy. The results showed Exo HER2 is a promissing biomarker for assessing tissue HER2 status in AGC and predicting clinical benefits of trastuzumab based therapy.